A social-technical harm-based taxonomy of online hate in South Africa - Omidosu, Joseph (Department of Information Systems, 2024)
Digital and social media provide online users with virtually unlimited interaction and instant communication to freely express their thoughts and opinions. Online users can communicate at no cost, write about anything, and quickly reach millions with expressions that can harm others. Attempts have been made to compare the impact of online hate with non-hate crimes, and it was argued that online hate could potentially be more harmful. It is becoming impossible to hear of a crime in our society without being linked to cyberspace. Reactive approaches through technological automation and users manually flagging incidents have been applied to remove online hate but possessitslimitations as online hate persists. Online hate continues to evolve and extend beyond what a silo approach can address. The study proposes a socialtechnical harm-based taxonomy by examining the problem definition of online hate in South Africa, identifying issues that influence online hate in South Africa and classifying harm from online hate targeted at online user characteristics, thereby addressing the research question, what harm results from the online user experience of online hate in South Africa? An umbrella Realism philosophical perspective and mixed method were adopted to collect and analyse the research data from a survey and Twitter big data. This approach was suitable as it posits that reality is independent of human perceptions and differences in perception exist. South Africa was adopted as a focal point due to limited data on online hate and evidence available to inform policy-making processes, decisions, and effective interventions by Government, civil society, or private organisations. Additionally, gaps exist in understanding the harm of online hate in countries like South Africa. The research contributes to the theory by developing a social-technical harmbased taxonomy to classify online hate. With limited knowledge of harm and online hate from an African country, the research provides empirical findings from South Africa. Adopting a mixed research methodology brings to the forefront the benefits of capturing data from multiple perspectives to assess online hate. The study contributes to practice by giving multi-perspective knowledge through exploring social, legal and technological insights. Understanding of harm from online hate was achieved, which is relevant for proactive awareness of harm from online hate, and Law enforcement and administrators can classify harm from online hate. With the knowledge of potential problems that trigger online hate, Government, Law enforcement, and administrators can provide more support during this period. The findings from South Africa show that individual characteristics such as age, albinism, birth, colour, culture, disability, ethnic or social origin, gender/gender identity, HIV status, language, nationality, migrant or refugee status, occupation/trade, political affiliation or conviction, race, religion, and sexual orientation can be targeted for online hate. Problems like social, political, racial and health-related issues were found to influence online hate in South Africa. Online users witness online hate and do not report the incidences because of a lack of knowledge of what to do, a lack of trust in reporting agencies, fear of the implication of reporting, and contextual awareness of the situation. The finding further provided evidence that online hate can have various negative consequences, including Social, Political, Financial, Reputational, Physical, and Psychological Harm. The study will help the government, statutory agencies, civic organizations, policymakers, and digital and social media administrators take proactive-preventive measures to combat the increasing menace of online hate.